Colon Classification for Library Science - Ranganathan, S. R. (Journal of Information and Knowledge, 1989)
Increase in the new subjects with literary warrant m the (BS) Library Science makes the schedules in Ed 1 to Ed 6 of CC inadequate. Many of, them are easily accommodated by the formation of compound isolates. Proliferation is greatest in (1P1) isolates. Therefore, quasi isolates are used to form isolates in (1P1). Advantage is also taken of the recent results in making the digits of an array range from a to (Z). Illustrations are given. The use of the Specials Division "9D Documentation", in the Schedule of Property Isolates, is illustrated. Examples of call numbers of some recent books are also given.